Tsunami risk perception, a state-of-the-art review with a focus in the NEAM region - Cugliari, Lorenzo; Cerase, Andrea; Amato, Alessandro (Frontiers in Earth Science, 2022)
Large-scale coastal urban sprawl, development of tourist accommodations and industrial maritime poles have highly increased the tsunami risk to people living and/or traveling along the coasts of our planet. The disastrous tsunamis in the Indian Ocean (2004) and in the Pacific Ocean (2011), as well as a suite of other damaging events worldwide, have encouraged International Institutions, first of all UNESCO IOC (Intergovernmental Oceanographic Commission), National Governments and Local Communities to implement Tsunami Warning Systems (TWS), to raise awareness on tsunami risk, and to create a multilevel risk governance. In this framework, research on tsunami risk perception plays a key role. The results of these studies should be taken into account in designing risk mitigation programs and tools (such as drills, activities with local communities, emergency plans, etc.). This paper presents a review of such studies, carried out in several countries worldwide through many thousands of interviews performed with different techniques. Most tsunami risk perception studies were carried out in the regions where the Indian Ocean Tsunami Warning System (IOTWS) and the Pacific Ocean one (PTWS) operate. In the NEAMTWS (North-East Atlantic, Mediterranean and connected seas TWS) region, only few specific studies were conducted, mostly within the EU-funded ASTARTE project (2013-2017) and more recently in a few extensive surveys on tsunami risk perception conducted in Italy between 2019 and 2021. Although the twenty-three studies analyzed in our review show a strong heterogeneity of methodological approaches and population samples, they allow us to outline some general considerations on tsunami risk as perceived by people in the different regions of the world. With the help of a SWOT analysis, we schematically summarized the emerging strengths, weaknesses, opportunities, and threats in the twenty-three papers, noting an increase in the number of such studies in the last five years. The surveys were mostly concentrated in high-risk areas and focused on local residents. Some differences emerged depending on the memory of past tsunamis, education level, and local cultures. This provides useful hints for sound citizen-based tsunami risk reduction actions, including improved risk communication aimed at increasing the resilience of tsunami-prone populations.